The Symbolism in KFC: A Semiotic Analysis of Branding Through Peirce’s Theory (Sastra Inggris UNPAM, 2025)
In the competitive fast-food industry, KFC's logo and slogan play a crucial role in brand identity and customer perception. This study examines the image of Colonel Sanders in the logo and the tagline,